Recurrent and reversible bilateral palmar blue discoloration following administration of liposomal daunorubicin-cytarabine (Vyxeos®) for acute myeloid leukemia with myelodysplasia-related changes. (August 2021) - Triesel, Katherine; Chiang, Timothy; Seabury, Robert; Miller, Christopher
Introduction: With novel treatment strategies for acute myeloid leukemia becoming more readily utilized in the clinical practice setting, new data on potential treatment-related adverse events also has become available. Case report: We present a patient case on a previously unreported potential adverse event related to liposomal daunorubicin-cytarabine administration. The patient experienced bilateral discoloration of the palms of his hands that resolved after completion of the treatment cycle, only to recur at cycle two of therapy. Management and outcome: No intervention was required as the condition resolved within a week of onset. Discussion: With newer therapeutic modalities becoming more used in the clinical setting, it is important to understand the potential risks of treatment-related adverse events that come with them. To our knowledge this is the first case reporting blue-skin discoloration related to liposomal daunorubicin-cytarabine.